Digital rights management system novel encryption and scrambling technique - Suon Vannak. (2011)
As demand for higher quality video media increases, the need for more efficient and more secured encryption method continues to escalate. Thus new encryption and scrambling algorithm, namely Puzzling encryption and Fully Format Compliant Selective Scrambling, have been proposed to address this need. There have been past researches done on both methods in comparison with various known encryption and scrambling methods implemented to explore their advantages. Puzzling encryption is a light weight compression-independent encryption algorithm. As the name sounds, the concept of this algorithm is like a puzzle where video stream will be encrypted in blocks and subsequently shuffled up like a puzzle. Format Complaint Selective Scrambling, on the other hand, is a joint compression and encryption algorithm. This algorithm involves scrambling of DC and AC coefficients and encryption of motion vectors’ signs. Doing so will enable the encrypted video stream to remain format compliant and thus playable by the player yet the video is indiscernible if not decrypted.